Hubungan Kompetensi Pedagogik Guru dengan Perubahan Perilaku Belajar Siswa Beragama Buddha - Banar Banar; Supartono Supartono; Julia Surya (Departement of Mathematics Education, 2023)
This study aims to measure how important pedagogical competence is in addressing student learning behavior at SMP Negeri 2 Susukan. This research is a quantitative research with a correlational approach, namely research that aims to find out whether or not there is an influence or relationship between two or more variables, and if there is a relationship, how big the relationship is. To collect data the researcher distributes questionnaires to students. This study involved 15 students. The results of the data analysis show a strong relationship between teacher pedagogical competence and student learning behavior.